An Hα survey of the host environments of 77 type IIn supernovae within z < 0.02. Issue 3 (29th April 2022) - Ransome, C L; Habergham-Mawson, S M; Darnley, M J; James, P A; Percival, S M
ABSTRACT: Type IIn supernovae (SNe IIn) are an uncommon and highly heterogeneous class of SN where the SN ejecta interact with pre-existing circumstellar media (CSM). Previous studies have found a mass ladder in terms of the association of the SN location with H α emission and the progenitor masses of SN classes. In this paper, we present the largest environmental study of SNe IIn. We analyse the H α environments of 77 type SNeIIn using continuum subtracted H α images. We use the pixel statistics technique, normalized cumulative ranking (NCR), to associate SN pixels with H α emission. We find that our 77 SNe IIn do not follow the H α emission. This is not consistent with the proposed progenitors of SNe IIn, luminous blue variables (LBVs) as LBVs are high-mass stars that undergo dramatic episodic mass loss. However, a subset of the NCR values follow the H α emission, suggesting a population of high-mass progenitors. This suggests there may be multiple progenitor paths with ∼60 per cent having non-zero NCR values with a distribution consistent with high-mass progenitors such as LBVs and ∼40 per cent of these SNe not being associated with H α emission. We discuss the possible progenitor routes of SNe IIn, especially for the zero NCR value population. We also investigate the radial distribution of the SNe in their hosts in terms of H α and r ′-band flux.